Quando as indumentárias da vida encontram refúgio na mortalha geracional : fantasmagorias da família (com)pactuam com seus herdeiros n'A Camisa do Marido, de Nélida Piñon - Assis, Guilherme Ewerton Alves de (2025)
Grounded in the theoretical foundations of Freudian psychoanalysis and the reverberations of its contemporary (dis)continuities — particularly drawing upon the contributions of Lacan, Mannoni, Abraham, Törok, Kaës, and Eiguer — this dissertation delves into the intricate processes of transgenerational psychic transmission, conceiving them as pivotal mechanisms in the fabric of unconscious pacts, narcissistic contracts, and psychic testaments that entangle subjects within the familial constellation. Within this symbolic architecture, descendants-heirs are inexorably traversed by immemorial legacies, woven through discourses, silences, prohibitions, and crypts, whose living-dead ghosts haunt lineages with their dissonant murmurs and insatiable demands. Language, erected as the primordial substance, precedes the very emergence of the subject, imposing upon them a phantasmatic filiation and a preconfigured desiring position, wherein the body and its symptoms become vehicles for inscribing the failures, lacks, and delusions of the parental order. Under this theoretical framework, the present study aims to analyze how the paternal function — as a structuring instance, though devoid of corporeality — persists, sustained by symbolic, affective, and imaginary devices orchestrated by the remaining members of the familial group. The investigation is anchored in the dissection of the short story A camisa do marido (“The Husband’s Shirt”), from the eponymous collection by Nélida Piñon (2014), whose fictional signs operate as revelatory mechanisms of the concealed gears that govern pacts of filiation, love, hatred, and psychic transmission. In the diegesis under scrutiny, following the patriarch’s death, the family (dis)organizes itself around the deceased’s shirt — an object that simultaneously embodies the attributes of relic, totem, invested phallus, fetish, and transitional object — thus establishing a psychic apparatus that names, anchors, and perpetuates the paternal function, while simultaneously catalyzing drive-based disputes among the surviving members. This research, therefore, seeks to understand how this symbolic artifact — “the father’s shirt” — operates within the plot as a condensatory sign of paradoxical functions: it assigns a place within the signifying chain; it garments the phallus, in the Lacanian sense; it is sustained as a transitional object, mediating presence and absence; and, moreover, it becomes a fetish — an object simultaneously of desire, prohibition, jouissance, and hatred. By literarily violating affective tombs, Piñon’s narrative enables an archaeological excavation of the family’s psychic underground, scrutinizing the enduring effects of myths, crypts, and specters that insidiously perpetuate themselves from generation to generation. Ultimately, this work conducts an inventory of the emotional ruins and inheritances that, while underpinning, simultaneously corrode the structures of kinship, weaving an ethnomythology of subjectivity in its most piercing, loving, and death-driven forms.